Effect of Cr6+ on the Properties of Alkali-Activated Slag Cement - Bo, Fu; Zhenyun, Cheng (Frontiers in Materials, 2021)
In order to investigate the effect of Cr6+ on the properties of alkali-activated slag cement (AAS), the effects of added dosage of Na2Cr2O4 on the setting time and compressive strength of AAS were measured. The leaching concentration of Cr6+ from AAS cement stone was measured using dual-beam UV-visible spectrophotometry. The effect of Na2Cr2O4 on the hydration kinetics of AAS cement was monitored by microcalorimetry and the corresponding kinetic parameters were analyzed. The pore solution from AAS was collected and analyzed using the high pressure press method. The effects of Na2Cr2O4 on the hydration products of AAS cement were observed and compared using X-ray diffraction (XRD) and scanning electron microscopy (SEM). The experimental results showed that the AAS hydration process was markedly affected by Na2Cr2O4 dosage. The setting time of AAS pastes was increased and the compressive strength of cement stones was reduced with increasing dosage of Na2Cr2O4. With the development of AAS hydration, the leaching concentration of Na2Cr2O4 gradually decreased. Na2Cr2O4 did not affect the dissolution of slag particles, but impeded the formation of C-S-H gel. The Cr6+ was immobilized chemically in the form of needle-like CaCrO4 particles formed by the chemical reaction between Na2Cr2O4 and Ca2+ leaching from the slag.